CAUSE FACTORS SYMBOLIC RESISTANCE OF GRAPHIC DESIGNERS IN DENPASAR CITY - I Ketut Sutarwiyasa; I Nyoman Darma Putra; A.A. Ngurah Anom Kumbara; Ni Made Wiasti (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2021)
The discourse of